Comprehensive Appraisal of COVID-19 Infection and Interaction with Domesticated and Wild Faunae - Berber, Engin; Sumbria, Deepak; Singla, Lachhman Das; Canakoglu, Nurettin (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Corona virus has a wide host range in animal kingdom including humans. Till 2002, the information related to human lethality due to  corona virus infection was very scanty and signs were uncommon. But early in 2002, appearance of a syndrome associated with severe  acute respiratory syndrome (SARS) has changed the whole scenario in relation to mortality in homo sapiens, and this SARS outbreaks  was followed by Middle East respiratory syndrome (MERS) in 2012 and currently in 2019-2020 we are dealing with corona virus disease  2019 (COVID-19) pandemic, caused by corona virus 2 (SARS-CoV-2) which is genetically closely related to SARS-CoV. SARS-CoV-2 spike  (S) protein interact with human angiotensin-converting enzyme 2 (ACE2) protein and gain excess to human cells for replication and  this action lead to devastating outcome in humans they infect along with excessive cytokine storm. In this current review we have  tried to give some update related to COVID-19 infection, major risk factor analysis playing an imperative role in changing the outcome  of disease. Further we have detailed the COVID-19 status in domestic and wild animals and how we can deal with understanding the  pathogenicity of COVID-19 by using various animal model.
Keywords: Animals; COVID-19; Human; Risk factors; Wild faunae